POTENSI PAKAN YANG MENGANDUNG SAMBILOTO (Andrographis paniculata) DAN DAUN JAMBU BIJI (Psidium guajava) UNTUK MENANGGULANGI BAKTERI Aeromonas hydrophila PADA IKAN BAUNG (Mystus nemurus) - Iesje Lukistyowati; Henni Syawal (Universitas Sriwijaya, 2013)
An effort to prevent Aeromonas hydrophila diseases in catfish (Mystus nemurus) performed using antibiotic was less safety. Prevention using natural substances mix with fishmeal could overcome the problem. The study was conducted to investigate fismeal potential containing herb of Sambiloto (Andrographis paniculata) and leaves of Jambu biji (Psidium guajava) with different dose given to fish aslong as 60 days. Treatment P1 (without sambiloto flour and jambu biji leaves), P1( 10 g of sambiloto flour + 10 g of jambu biji flour/kg of fish meal), P2 (20 g of sambiloto flour + 20 g of jambu biji flour/ kg of fish meal), P3 (30 g of sambiloto flour + 30 g of jambu biji flour/ kg of fish meal). After 60 days, infection of Aeromonas hydrophila through intraperitonial with concentration of 108 cell/ml and dose of 0,1ml/fish was conducted. Result of study show that catfish feed with fismeal containing sambiloto and jambubiji could increase survival rates and growth rates (P˂0,05), but fishmeal containing sambiloto and jambu biji leaves was not effective to privent diseases coused by Aeromonas hydrophila on catfish (Mystus nemurus). Keywords : Andrographis paniculata, Psidium guajava, Aeromonas hydrophila, catfish (Mystus nemurus)